Pre-service teachers’ language mindset and its impact on the engagement and persistence in their language pedagogical studies : a study conducted in EFL teacher education in Finland - Perera, Sonali (2024)
In the mindset research field, pre-service teachers’ mindsets are understudied. Their beliefs about the malleability of their English as a Foreign Language (EFL) ability (that it is a predetermined trait – fixed language mindset (FLM), a changeable trait – growth language mindset (GLM) or an intermediate state – mixed language mindset (MLM)), also known as language mindsets are likely to impact the levels of engagement and persistence in their EFL pedagogical studies. This study examines the impact of language mindsets of the pre-service teachers on the engagement and persistence in their EFL pedagogical studies.